Validety of total laryngectomy Under local anaesthesia - Al-rubeai, Thamir M.; Bader, Hani M.; . Ali, Samar F (AL-Kindy College Medical Journal, 2012)
BackgroundCarcinoma of the larynx represent 10% of head & neck malignancies. The treatment of advanced carcinoma of larynx may include partial or total laryngectomy, with or without laser , radiotherapy,and or chemotherapy . Carcinoma of the larynx usually affect old age , heavy smoker with possible risk of pulmonary diseases & ischemic heart disease , which add risk to the general anaesthetic complication operative & postoperative - Objectives this study was designed to assess the feasibility of total laryngectomy under local anaesthesia in medically unfit patients for general anaesthesia & to re-establish practice doing total laryngectomy under local anaesthesia in those patients. Methods a prospective study on 12 patients who underwent total laryngectomy under local anaesthesia in the otolaryngology department at Al-Jirahat hospital over a period from September 2007 to the end of July 2010. Results all patients tolerated the surgical procedure under local anaesthesia without disturbing the general condition of the patient, or the technique of surgery , with good postoperative recovery & early mobility of patient . Conclusion total laryngectomy can be done under local anaesthesia in case the patient is medically not fit for general anaesthesia , & in some other selected cases .